Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let a triangle $ABC$. $M$ is a point inside triangle. construct the line through M perendicular to $MA, MB, MC$ and intersect $BC, CA, AB $ at $A_0,B_0,C_0$ respectively. Prove that $A_0,B_0,C_0$ are collinear

I really don't know where to start. Menelaus? Thank enter image description here

share|improve this question
    
In what kind of school is this a "homework"? It looks more difficult than what can be assigned in an ordinary class. –  zyx Jun 11 '13 at 2:33
add comment

2 Answers

Let $A(0,a),B(b,0),C(c,0),M(x_1,y_1)$

$k_{AM}=\dfrac{y_1-a}{x_1},A_0M: y-y_1=\dfrac{x_1}{a-y_1}(x-x_1) \to A_0 \left(\dfrac{x_1^2+y_1^2-ay_1}{x_1},0\right)$

$k_{BM}=\dfrac{y_1}{x_1-b},B_0M:y-y_1=-\dfrac{x_1-b}{y_1}(x-x_1),AC:y=-\dfrac{a}{c}(x-c) \to B_0 \left(\dfrac{c(y_1^2+x_1^2-ay_1-bx_1)}{cx_1-ay_1-bc},-\dfrac{a(y_1^2+x_1^2-cx_1-bx_1-bc)}{cx_1-ay_1-bc} \right)$

$k_{cM}=\dfrac{y_1}{x_1-c},C_0M:y-y_1=-\dfrac{x_1-c}{y_1}(x-x_1),AB:y=-\dfrac{a}{b}(x-b) \to C_0 \left(\dfrac{-b(y_1^2+x_1^2-ay_1-cx_1)}{bx_1-ay_1-bc},-\dfrac{a(y_1^2+x_1^2-bx_1-cx_1-bc)}{bx_1-ay_1-bc} \right)$

$k_{A_0B_0}=\dfrac{\dfrac{a(y_1^2+x_1^2-cx_1-bx_1-bc)}{cx_1-ay_1-bc}}{\dfrac{x_1^2+y_1^2-ay_1}{x_1}-\dfrac{c(y_1^2+x_1^2-ay_1-bx_1)}{cx_1-ay_1-bc}}=\dfrac{ax_1(y_1^2+x_1^2-cx_1-bx_1-bc)}{y_1(a^2y_1+abc-ax_1^2-ay_1^2-bcy_1)}$

$k_{A_0C_0}=\dfrac{\dfrac{a(y_1^2+x_1^2-cx_1-bx_1-bc)}{bx_1-ay_1-bc}}{\dfrac{x_1^2+y_1^2-ay_1}{x_1}-\dfrac{b(y_1^2+x_1^2-ay_1-cx_1)}{bx_1-ay_1-bc}}=\dfrac{ax_1(y_1^2+x_1^2-cx_1-bx_1-bc)}{y_1(a^2y_1+abc-ax_1^2-ay_1^2-bcy_1)}$

$k_{A_0B_0}=k_{A_0C_0} \implies A_0,B_0 ,C_0 $ co-line .

BTW, the mid points of $AA_0,BB_0,CC_0$ are also co-line.

share|improve this answer
add comment

Let $M$ be the origin and consider the three vertices $A$, $B$, $C$ as vectors $a$, $b$, $c$. You get the vector $a'=(1-t)b+t c\>$ representing $A_0$ by solving $$\bigl((1-t)b+tc\bigr)\cdot a=0$$ for $t\in{\mathbb R}$ and obtain $$a'={(a\cdot b)c-(a\cdot c)b\over a\cdot(b-c)}\ .$$ Using analogy for $b'$ and $c'$ it follows that $$\bigl(a\cdot(b-c)\bigr) a'+\bigl(b\cdot(c-a)\bigr) b'+\bigl(c\cdot(a-b)\bigr) c'=0\ .$$ But $\lambda a'+\mu b'+\nu c'=0$ with $\lambda+\mu+\nu=0$ means that $a'$, $b'$, and $c'$ are collinear.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.